A Posteriori Error Estimates in Adini Finite Element for Eigenvalue Problems (Journal of Computational Mathematics, 2000)
In this paper, we discuss a posteriori error estimates of the eigenvalue $λ_h$ given by Adini nonconforming finite element. We give an asymptotically exact error estimator of the $λ_h$. We prove that the order of convergence of the $λ_h$ is just 2 and the $λ_h$ converge from below for sufficiently small $h$.
Keywords: eigenvalue; nonconforming finite element; error estimate.